2020
DOI: 10.31025/2611-4135/2020.13943
|View full text |Cite
|
Sign up to set email alerts
|

Scale and Impacts of Livelihoods Development on Women Empowerment in the Solid Waste Sector of Jordan

Abstract: The present study outlines a cohesive compilation of analysis of the involvement of women in decision-making and leadership in the solid waste sector in Jordan. The socio-economic challenges have been catalyzed by the influx of Syrian refugees into the host communities and camps in Jordan. Hence, deterioration of municipal solid waste services have centered on and proposed that women engagement in the Solid Waste (SW) sector to provide opportunities that aim to improve livelihoods by prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Alongside technical interventions, it is advisable to take specific actions to improve the public awareness and the willingness of the local communities in Jordan to participate in waste recycling and separation practices, as this is usually not the case (Hararah et al, 2016; Tarawneh and Saidan, 2013). Moreover, the engagement of women in SW recycling was demonstrated to be beneficial (Saidan et al, 2020a).…”
Section: Resultsmentioning
confidence: 99%
“…Alongside technical interventions, it is advisable to take specific actions to improve the public awareness and the willingness of the local communities in Jordan to participate in waste recycling and separation practices, as this is usually not the case (Hararah et al, 2016; Tarawneh and Saidan, 2013). Moreover, the engagement of women in SW recycling was demonstrated to be beneficial (Saidan et al, 2020a).…”
Section: Resultsmentioning
confidence: 99%
“…Saidan et al (2017) highlight how recycling, as part of solid waste management, provides employment and a livelihood for vulnerable social groups such as refugees. In this context, Saidan et al (2020) stress how recycling helps women empowerment, especially in the case of women refugees in Jordan. For instance, the "Cash for Work" initiative taken in refugees' camps helped educate Syrian refugee women to sort dry wastes on a household level.…”
Section: Sustainable Practices In Refugee Camps and Basic Human Right...mentioning
confidence: 99%
“…(2017) highlight how recycling, as part of solid waste management, provides employment and a livelihood for vulnerable social groups such as refugees. In this context, Saidan et al . (2020) stress how recycling helps women empowerment, especially in the case of women refugees in Jordan.…”
Section: Sustainable Practices In Refugee Camps and Basic Human Right...mentioning
confidence: 99%
“…Similarly, a study on the scale and impacts of livelihoods development on women empowerment in the solid waste sector in Jordan showed that projects implemented by international organizations have contributed to women's empowerment by granting them access to livelihoods and expertise and strengthening their roles in these projects (Saidan, Abu Drais, AL-Manaseer, Alshishani, & Linton, 2020). This study is also problematic as it only interviewed experts and NGO workers, without asking the women about their experiences.…”
Section: Jordanmentioning
confidence: 99%